Falacias no planejamento do legado esportivo da Copa do Mundo FIFA nas doze cidades-sede no Brasil - Paiva, Rodrigo da Silva (2018)
In Brazil, the public policies of sports and leisure have been targeted, since the realization of the Pan American Games of 2007, by the explicit goal of designing internationally the country in political and economic areas. The country hosted, in the range of a decade, the biggest sporting events of the Earth: Military games (2011), Confederations Cup (2013), F.I.F.A. World Cup (2014), America’s Cup (2015) and Olympic Games (2016). The argument adopted by the managers of the different sublevels of government, explained in application documents of the Ministry of Sports, to legitimize the assumption of an agenda too committed to sports, was that the social legacy of sporting mega events would a modernization of infrastructure, upgrading of services, social mobilization, economic decentralization, stimulation to the many forms of innovation, commitment to the environment and sustainability, improvement of transparency in public management and dissemination of sports. Taking this last aspect as main reference, the objective of this study is to verify whether, and to what extent, the twelve host cities in Brazil that received the F.I.F.A. World Cup planned programs of democratization as the legacy sports mega event. For the study, were collected, analyzed and discussed the data gathered between 2012-2016 in a national project, World Cup cities, of note, proposing and monitoring of documents prepared for the legacy of the World Cup, from carrying out a program led by a sports institution of the third-sector, financed with public money and made possible through tax waiver for the private sector, through the law of Incentive to the sport. Meetings were held with all the sports Secretaries of host cities and other sectors of society. Compare arrays of responsibilities and the legacy plans produced in Cities. The detailed analysis of a set of indicators agreed by public managers, of the host cities, related to the sporting legacy, namely, investment in infrastructure, professional training for the universalization of access to sports, resizing of policies to encourage the social sport to the detriment of the elite sport and performance and development of programs of universalizing access to sport in the school environment, showed that no host city of FIFA World Cup designed any effective actions for the sporting legacy. The Developed action plans did not guarantee the representation of diverse interests of leather sports actors of each locale. Sports managers in multiple sublevels of Government have shown little or no commitment to the sporting legacy. The elaborate plans even became part of the political agenda of sports of host cities. The World Cup Cities Project, with obsolete results, could never have been accomplished and, If the investments that consumed were directed to the direct care of children and young people in long-term sports programs would decrease the contradiction as fallacious speech sporting legacy of the mega event and the implementation of public policies for universalization of access to sports